PERGESERAN MAKNA JUAL BELI DALAM PRAKTIK MURĀBAḤAH PERBANKAN SYARIAH MELALUI ANALISIS KRITIS PRINSIP KEPEMILIKAN DAN RISIKO - Muhammad Abrar Azizi (Mukhtasab: Journal of Economics and Islamic Business, 2026)
Murābaḥah practices in Islamic banking have become the most dominant financing instrument, yet they raise academic concerns regarding their conformity with the concept of sale (bay‘) in Islamic jurisprudence (fiqh al-mu‘āmalāt). Normatively, murābaḥah is a sale contract that requires genuine ownership and risk-bearing by the seller prior to the transfer of goods to the buyer. However, contemporary Islamic banking practices often operationalize murābaḥah in a manner resembling fixed-margin financing rather than a genuine sale transaction. This condition indicates a shift in the meaning of sale from an asset-based transaction to a financing-oriented mechanism. This study aims to analyze the shift in the meaning of sale in Islamic banking murābaḥah by emphasizing the principles of ownership and risk as the main analytical framework. The research employs a qualitative normative-critical approach, utilizing secondary data sources such as murābaḥah contract documents, Shariah rulings, Islamic banking regulations, and classical as well as contemporary fiqh al-mu‘āmalāt literature. The analysis is conducted by comparing the normative concept of murābaḥah with its actual implementation in Islamic banking practices. The findings reveal that ownership and risk in murābaḥah practices tend to be formalistic and administrative, while economic risks related to the transaction are largely transferred to customers. This pattern confirms the shift of murābaḥah from a sale contract toward a financing instrument. Theoretically, this study contributes to contemporary Islamic jurisprudence discourse, while practically it provides insights for Islamic banks and regulators to reconstruct murābaḥah practices in order to align them more closely with the substantive principles of sale and the objectives of Islamic economics.